Immunoelectrophoresis of avian viral proteins in a phosphate-buffered system - Freidlin, P.J; Bock, R; Inbar, A; Samberg, Y (Avian diseases, 1985)
Avian influenza and hemorrhagic enteritis viral preparations were immunoelectrophoresed in a phosphate-buffered system. Excellent separation and resolution of viral proteins were achieved. Reasons are given why this method might be preferred over the conventional method employing a veronal (barbital)-buffered system.